The Efectiveness of Implementation Round Robin Technique in The Teaching of Writing for The Third Semester PBI Students of Pancasakti University Academic Year 2015/2016 - Nur Laila Molla (Universitas Pancasakti Tegal, 2016)
The objective of this research is to find out correlation whether Round Robin Technique is effective to use in the teaching of writing for the third semester PBI students of Pancasakti University academic year of 2015/2016. The population of this research is the third semester PBI students of Pancasakti University academic year of 2015/2016. The number of population is ninety five students from five classes. This research is conducted by using two group designs; the first group is called experimental group that is taught using Round Robin Technique, while the second group is called control group that is taught using Four Square Technique. The sample is taken by using cluster random sampling. Each group of samples consists of 30 students. The instrument used in this research is writing test in the form of guided. The test is conducted after the two groups get treatment for 4 meetings. The test is carried out to find out whether students who are taught by using Round Robin Technique get a better writing score achievement than students who are taught using Four Square Technique. Then, the writing test is assessed by using rubric of Brown's writing scoring. Data analysis of this research is tested by using t-test in order to find out whether the research hypothesis is accepted or not. Based on the computation, the t-ratio is 3.443. It is consulted with t-table on the significant level (a) of 5% and the degree of freedom (df) is 58. The t-table obtained is 1.672. It shows that t-ratio is higher than t-table (3.443 > 1.672), so the hypothesis of the research is accepted. The conclusion of this research is there is correlation between Round Robin Technique and Writing Achievement. Students who are taught using Round Robin Technique get a better writing achievement than students who are taught using Four Square Technique. Round Robin Technique is proven to be one of the effective techniques to make students interested in learning writing and boost the achievement. It also makes the situation in the classroom more adaptable, so it prevents the students from getting bored. English teachers are suggested to apply Round Robin Technique in the teaching of writing. They should also motivate their students to work as a team to make learning writing more fun. Furthermore, it is better for teachers to give their students more and more writing assignments and evaluations to make them accustomed to writing and also achieving higher academic score